Total Quality Management for High Quality Education Strategy at Pondok Modern Darussalam Gontor Ponorogo - Mardiyah, Mardiyah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
Quality education is of great concern to many people around the world. In the highly competitive education sector, the success of Islamic boarding schools depends on the quality of education. Total Quality Management (TQM) is a reference for managing quality-based educational institutions. Pondok Modern Darussalam Gontor Ponorogo is one of the Islamic boarding school educational institutions that now exists and has produced active graduates. This cannot be separated from good and quality education management. This study aims to analyze and reveal a TQM-based quality strategy at Pondok Modern Darussalam Gontor. Based on the study, it was found that the implementation of Total Quality Management (TQM) in Islamic boarding schools is carried out by promoting "quality" as a business strategy oriented towards customer satisfaction based on Islamic religious values. For this purpose, quality tools and techniques are used to identify and solve problems creatively to achieve quality in Islamic boarding schools. The study concluded that Total Quality Management (TQM) can be a strategy for managing quality-based Islamic boarding schools.